INDIKASI MACHIAVELLIANISM DALAM PEMBUATAN KEPUTUSAN ETIS AUDITOR PEMULA - Ananda, Febryandhie; Zulvia, Dewi (Jurnal Benefita, 2018)
This research is a continuation from the previous research who find inconsistent results. The purpose of this study is to examine the machiavellianism relationship with ethical decisions in earnings management in Indonesia in two forms of manipulation, namely manipulation of operations and accounting manipulation. Data collection methods in this study used as many as 34 respondent. Machiavellianism does not affect the ethical decision of earnings management in the Public Accountant Office in West Sumatra. Independent accountants who support are those who have the majority of first-level education with an average age of 26-35 years, who are generally male and have more than 10 years of experience. This is because the customary system of ABS - SBK (Adat Bersandi Syara '- Syara' Bersandi Kitabullah) in West Sumatra has an impact on the machiavellian nature of accountants, and there is a significant difference between operating manipulation and accounting manipulation. Penelitian ini merupakan kelanjutan dari penelitian sebelumnya yang menemukan hasil yang tidak konsisten. Tujuan dari penelitian ini adalah untuk menguji hubungan machiavellianism dengan keputusan etis dalam manajemen laba di Indonesia dalam dua bentuk manipulasi, yaitu manipulasi operasi dan manipulasi akuntansi. Metode pengumpulan data dalam penelitian ini menggunakan sebanyak 34 responden. Machiavellianism tidak mempengaruhi keputusan etis manajemen laba di Kantor Akuntan Publik di Sumatera Barat. Akuntan independen yang mendukung adalah mereka yang memiliki mayoritas pendidikan tingkat pertama dengan usia rata-rata 26-35 tahun, yang umumnya laki-laki dan memiliki lebih dari 10 tahun pengalaman. Hal ini karena sistem adat ABS - SBK (Adat Bersandi Syara '- Syara' Bersandi Kitabullah) di Sumatera Barat memiliki dampak pada sifat machiavellian akuntan, dan ada perbedaan yang signifikan antara manipulasi operasi dan manipulasi akuntansi.